(untitled) (Texas Journal of Engineering and Technology, 2023)
Currently, air-separating compressors are widely used in many industries in the Republic of Uzbekistan. Air separation plays a very important role in the industry its role in the development of the metallurgical industry is considered to be large and not only the required air compressor cooling equipment and compressed air for cooling plant, but also the raw material needed for separation the plant is the main device in the air separation plant. Usage most of the air compressor is very wide used in important departments such as metallurgy, oil and chemical industry. An air compressor system is a complex time-varying, delayed, and nonlinear system. Defects in content the traditional control method and the controller leads to instability of the pressure of the released compressed air air compressor in conditions of volatile gas consumption, wide range fluctuations that sometimes occur, for gas consumption in the industrial sector creates a chaotic environment. That is why, the working condition of the air compressor will be unstable. In general, the electricity consumption of air the compressor system operates at steady state and it is twenty percent of the total energy consumption affects the economic condition of the enterprise. In addition, energy consumption unstable condition will be more. This also leads to wastage of resources and causes more energy consumption. Therefore, the guarantee the output pressure of the air compressor system is stable it is extremely important to increase efficiency and energy saving will be necessary for the general air separation system. This turbine compressor system was taken as the research object and analyze its characteristics and control requirements. Technological control technology applied to the system, ECS-500 the SUPCON system was used for air conditioning compressor system and monitoring real time values important parameters of various components were calculated. According to the working characteristics of the air compressor system, technical system control theory, as one modern control theories were applied to the constant and pressure control system for technical pressure design set by the manager. The simulation results showed that the controller and not only more convenient and efficient, but that provided a specific guideline value and reference for and studies were conducted on the control of other parameters of the air compressor system.